2017
DOI: 10.15407/agrisp4.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Biological efficiency of citrates of microelements in animal breeding

Abstract: To ensure normal functioning of the organism of animals, the maintenance of their vital functions, the growth and development of the young animals, their productive and reproductive capacities, it is necessary to ensure their full nutrition. Unbalanced mineral nutrition in the diet of the animals leads to the impairments of mineral metabolism in their body. One of the most promising way of obtaining micronutrients with guaranteed safety and bioticity is the use of the achievements of nanotechnology and bioorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
0
8
0
3
Order By: Relevance
“…Taking into account the broad spectrum of biological activity of mineral and organic compounds of I, Se, and S, research on the influence of these citrates and other trace elements on the organism of animals was begun in Ukraine (Dolaychuk et al, 2015;Iskra et al, 2017;Stoika et al, 2017). The results of earlier studies indicate the pronounced biological effect of these compounds in low concentrations without manifestations of toxic reaction in the body of rats (Dolaychuk et al, 2015;Fedoruk at al., 2018) and cows, pigs, rabbits, bees (Iskra et al, 2017;Malavolta & Mocchegiani, 2018). Studies by other authors (Mohapatra et al, 2014;Yausheva et al, 2016;Landry et al, 2017) stipulate a stimulating metabolic effect of nanosized compounds of biotic mineral elements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account the broad spectrum of biological activity of mineral and organic compounds of I, Se, and S, research on the influence of these citrates and other trace elements on the organism of animals was begun in Ukraine (Dolaychuk et al, 2015;Iskra et al, 2017;Stoika et al, 2017). The results of earlier studies indicate the pronounced biological effect of these compounds in low concentrations without manifestations of toxic reaction in the body of rats (Dolaychuk et al, 2015;Fedoruk at al., 2018) and cows, pigs, rabbits, bees (Iskra et al, 2017;Malavolta & Mocchegiani, 2018). Studies by other authors (Mohapatra et al, 2014;Yausheva et al, 2016;Landry et al, 2017) stipulate a stimulating metabolic effect of nanosized compounds of biotic mineral elements.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by other authors (Mohapatra et al, 2014;Yausheva et al, 2016;Landry et al, 2017) stipulate a stimulating metabolic effect of nanosized compounds of biotic mineral elements. Adequate physiological ratios of I, Se, Cr, Ge citrates, for their combined use in laboratory animals were experimentally determined (Dolaychuk et al, 2015;Iskra et al, 2017). Feeding mature, 4-8-month-old, rats (feeding started at 4 months and lasted till the end of the 8 th month) and young, 0-4-monthold, rats (feeding started at birth and lasted for 4 months) with "nanoaquacitrates" of germanium, chromium, and selenium causes an increase of physiological reactivity in their bodies (Dolaychuk et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IMPACT OF FEEDING MALE RATS F 2 WITH DIFFERENT DOSES OF GERMANIUM CITRATE biological role of these organo-compounds and their interaction with other macro-and trace elements and their impact on their distribution in the organism and its organs are actively studied as well. In particular, our earlier research [7,8] showed that the administration of germanium citrate, obtained via the erosive and explosive ablation with electro-impulse, caused a number of biological effects in the organism of rats. This may have found its cause in the fact that germanium (Ge) has an immuno-stimulating effect, enhances transport and transfer of Ɉ 2 and ensures the decrease of hypoxia at tissue level [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In Ukraine, the number of thyroid diseases has almost doubled in recent deca des, which is associated with the lack of proper systemic prevention of iodine deficiency [3]. Therefore, in human nourishment and animal nutrition, salt, mineral, and organic iodine compounds are used to be added to water, various components of food and feed ration [4][5][6][7].…”
mentioning
confidence: 99%